Kesiapan Kompetensi Profesional Pustakawan dalam Pembangunan dan Pengembangan iKuansing di Dispersip Kuansing - Marlinda; Thoriq Tri Prabowo (THE LIGHT : Journal of Librarianship and Information Science, 2022)
This study aims to determine the readiness of the professional competence of librarians in the development and development of iKuansing in the Dispersip Kuansing. The results of this study are presented in accordance with Sudarsono's theory, namely the readiness of the professional competence of librarians. The method used in this research is a descriptive qualitative research method with data collection techniques of observation, interviews and documentation. In this study, researchers used data analysis techniques through three stages, namely data reduction, data presentation, and verification/drawing conclusions. To test the credibility of the data, triangulation technique was used. The result of this research is qualitative research. Data analysis is descriptive. The research subject is the iKuansing application, staff and librarians at Dispersip money. The object of this research is the readiness of the librarian's professional competence in the development and development of iKuansing. The results of this study are the iKuansing in the Dispersip Kuansing consisting of 10 indicators, according to the informant's perception 8 of the competencies already possessed by the librarian are: librarians have been able to create and manage efficient digital technology, librarians are able to monitor, filter, and select up-to-date, librarians have knowledge and management skills of Pusdokinfo, librarians are able to provide user education, librarians use information technology for information distribution, librarians able to develop information products that can be used anywhere, librarians are able to continuously update information services, librarians are able to understand the ethics of cyberspace already owned by librarians. Meanwhile, there are two indicators that do not have readiness, namely: librarians have not been able to assess the needs of users on a regular basis because librarians have not provided space for users to provide input and suggestions as evaluation material for librarians and libraries. Librarians have not been able to communicate information services to the leadership because iKuansing is an activity program that has been designed by the library planning department.